Catalytic gasoline particulate filter
By coating the main catalytic layer and the secondary functional material layer on the gasoline particulate filter, the problem of difficult to meet the particulate emissions and high conversion rates of HC, NOx and CO in the prior art is solved, and an efficient catalytic filtration effect is achieved.
Patent Information
- Application Number
- CN202080030407.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-04-22
- Filing Date
- 2020-04-20
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2040-04-20
AI Technical Summary
The prior art is difficult to achieve efficient conversion of HC, NOx and CO in gasoline engine exhaust while meeting strict particulate emission standards.
A catalytic particulate filter is employed, which includes a primary catalytic layer and a secondary functional material layer coated on the surface of the gasoline particulate filter. The primary catalytic layer contains a high surface area refractory metal oxide support and a platinum group metal, and the secondary functional material layer is placed on top of the primary catalytic layer to improve the catalytic efficiency of the filter.
The filtration efficiency and catalytic efficiency of the catalytic particulate filter are significantly improved, and the particulate matter can be effectively removed and the conversion of HC, NOx and CO are improved, meeting strict emission standards.
Smart Images

Figure CN113710351B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to the entire contents of International Application No. PCT / CN2019 / 083641 filed on April 22, 2019. Technical Field
[0003] The present invention relates to a catalytic particulate filter for exhaust gas treatment of a gasoline engine, which provides improved catalytic efficiency together with a high efficiency filter.
[0004] background
[0005] Particulate emissions from gasoline engines are being regulated by legislation, including the Euro 6 (2014) standard. Certain gasoline direct injection (GDI) engines have been developed with operating procedures that result in the formation of fine particles. Aftertreatment systems for gasoline engines are required to meet particulate matter standards. Particulates produced by gasoline engines such as GDI engines tend to be finer and less numerous than those produced by diesel lean burn engines. This is due to the different combustion conditions in diesel engines compared to gasoline engines. For example, gasoline engines operate at higher temperatures than diesel engines. The hydrocarbon composition of gasoline engine emissions is also different compared to diesel engines.
[0006] The emission of unburned hydrocarbons, carbon monoxide and nitrogen oxide pollutants continues to be regulated. Catalytic converters containing three-way conversion (TWC) catalysts are accordingly located in the exhaust tract of internal combustion engines. Such catalysts promote the oxidation of unburned hydrocarbons and carbon monoxide in the exhaust stream by oxygen and the reduction of nitrogen oxides to nitrogen.
[0007] A catalytically active particulate filter is provided in US Pat. No. 8,066,963. The particulate filter of US Pat. No. 8,066,963 comprises a filter body and a catalytically active coating consisting of two layers. The layers are arranged so that the second layer is in direct contact with the incoming gas and completely covers the first layer on the exhaust side. Both layers contain aluminum oxide. The first layer contains palladium. The second layer contains rhodium.
[0008] A catalyzed particulate trap is provided in U.S. Pat. No. 8,173,087, which includes a TWC catalyst coated on or within the particulate trap. The TWC catalyst may be coated on the inlet side, outlet side, or both of the filter. US 8173087 states that some particulates from a GDI gasoline engine may avoid being captured by the filter by flowing through the filter wall when the filter is fresh and that to address initial filter efficiency issues, a thin layer of catalytic washcoat may be coated on the filter wall.
[0009] US Patent No. 8,815,189 also provides a gasoline engine emission treatment system with a particulate filter. The three-way conversion (TWC) catalyst or oxidation catalyst of US 8815189 is coated on and inside the particulate filter, and the coated porosity of the particulate filter is substantially the same as its uncoated porosity.
[0010] Gasoline engines typically operate under near stoichiometric reaction conditions, which oscillate or fluctuate slightly between rich and lean air to fuel ratios (A / F ratios) (A / F=14.7 or λ=1). "Stoichiometric" is used herein to refer to gasoline engine conditions, indicating that the A / F ratio oscillates or fluctuates near stoichiometry. As is well known in the art, when operating under stoichiometric premixed gasoline / air, PM levels are comparable to non-fuel levels; therefore, combustion of a premixed stoichiometric mixture does not significantly produce particulates. For rich premixed gasoline / air, PM increases dramatically when λ is less than 0.7 to 0.8.
[0011] On December 23, 2016, the Ministry of Environmental Protection of the People's Republic of China (MEP) announced the final legislation for the National VI Limits and Measurement Methods for Light Vehicle Emissions (GB18352.6-2016; hereinafter referred to as National VI), which is much stricter than the National V emission standards. In particular, the National VIb aims to reduce THC and CO emissions by 50% and NOx by 42% from the National V level. In addition, National VIb incorporates limits for nitrous oxide (N2O) and particulate matter (PM); and adopts on-board diagnostic (OBD) requirements. In addition, it is specified that the test should be tested under the World Harmonized Light Vehicle Test Cycle (WLTC). The WLTC includes many steep accelerations and long high-speed requirements, which require high power output, which may cause long (e.g., >5 seconds) "open loop" conditions (because the fuel paddle needs to be fully pushed down) under rich (λ<1) or deep rich (λ<0.8) conditions.
[0012] However, as standards become more stringent, there is a need to provide a catalytic filter that provides improved catalytic efficiency together with a high efficiency filter so that regulated HC, NOx and CO conversion rates can be achieved while satisfying particulate matter emissions.
[0013] Overview
[0014] The present invention relates to a catalytic particulate filter for the exhaust gas of a gasoline engine. The catalytic particulate filter provides improved catalytic efficiency together with a high efficiency filter.
[0015] Various aspects include a catalyzed particulate filter for exhaust gas from a gasoline engine, comprising: a gasoline particulate filter (GPF); a primary catalytic layer coated on or within an inlet side, an outlet side, or both sides of a GPF surface, the primary catalytic layer comprising a first composition, wherein the first composition comprises a first hydrothermally stable support material; and a first platinum group metal (PGM); and a minor function material layer disposed on or within an inlet side, an outlet side, or both sides of a GPF surface; the minor function material layer comprising a second composition.
[0016] Other aspects include a method for treating exhaust gas from a gasoline engine, comprising providing a particulate filter; and directing exhaust gas from the engine through the particulate filter. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 A graph showing gas phase pollution emissions in a fresh state for a catalyzed gasoline particulate filter according to an embodiment of the present invention and a prior art particulate filter;
[0019] Figure 2 a graph showing the filtration efficiency of a catalytic gasoline particulate filter according to an embodiment of the present invention and a prior art particulate filter;
[0020] Figure 3 A graph showing gas phase pollution emissions of a catalytic gasoline particulate filter in a fresh state according to an embodiment of the present invention;
[0021] Figure 4 a graph showing the filtration efficiency of a catalyzed gasoline particulate filter according to an embodiment of the present invention;
[0022] Figure 5 A graph showing the filtration efficiency of a catalyzed gasoline particulate filter according to an embodiment of the present invention and a prior art particulate filter.
[0023] Details
[0024] Before describing several exemplary embodiments of the present invention, it should be understood that the present invention is not limited to the details of construction or process steps set forth in the following description. The present invention is capable of other embodiments and of being practiced or carried out in various ways.
[0025] With respect to terms used within this disclosure, the following definitions are provided.
[0026] Throughout the description, including the claims, the terms "comprising a" or "including an" should be understood to be synonymous with the term "comprising at least one", unless otherwise stated, and "between" or "to" should be understood to include limits.
[0027] The terms "a," "an," and "the" are used to refer to one or more (ie, to at least one) of the grammatical objects of the clause.
[0028] The term "and / or" includes the meanings of "and", "or" and all other possible combinations of elements related to this term.
[0029] Unless otherwise indicated, all percentages and ratios are by weight.
[0030] A typical catalytic particulate filter suitable for use with gasoline includes a gasoline particulate filter (GPF); and a TWC catalyst coated on or in the inlet side, outlet side, or both sides of the GPF surface for treating an exhaust stream containing hydrocarbons, carbon monoxide, nitrogen oxides, and particulates. We surprisingly found that in addition to the primary catalytic layer coated on or in the GPF surface, placing a secondary functional material layer in particulate form on or in the GPF surface without excessively increasing back pressure together with a high efficiency filter provides significantly improved catalytic efficiency.
[0031] Therefore, according to one aspect of the present invention, there is provided a catalytic particulate filter for gasoline engine exhaust, comprising:
[0032] (1) Gasoline particulate filter (GPF);
[0033] (2) a primary catalytic layer coated on or within the inlet side, outlet side, or both sides of the GPF surface, the primary catalytic layer comprising a first composition, wherein the first composition comprises a first support material; and a first platinum group metal (PGM); and
[0034] (3) a secondary functional material layer disposed on or within the inlet side, outlet side, or both sides of the GPF surface; the secondary catalytic layer comprises a second composition;
[0035] (4) wherein the primary catalytic layer has a higher loading than the secondary functional material layer;
[0036] (5) A secondary functional material layer is placed on top of a primary catalytic layer, or vice versa.
[0037] The term "support" in the catalyst support coating layer refers to a material that receives precious metals, stabilizers, promoters, binders, etc. by combination, dispersion, impregnation or other suitable methods. Examples of supports include, but are not limited to, high surface area refractory metal oxides and composites containing oxygen storage components. High surface area refractory metal oxide supports refer to materials with a surface area greater than High surface area refractory metal oxide supports such as alumina support materials (also known as "gamma-alumina" or "activated alumina") typically exhibit a surface area in excess of 60 m2 / g ("m 2 / g”), usually up to about 200m 2 / g or more of fresh BET surface area. Such activated aluminas are typically mixtures of gamma and delta phases of alumina, but may also contain significant amounts of eta, kappa, and theta alumina phases. Refractory metal oxides other than activated aluminas may be used as supports for at least some of the catalytic components in a given catalyst. For example, alpha-alumina, bulk ceria, zirconia, silica, titania, rare earth metal oxides other than ceria, and other materials are known for this purpose.
[0038] In one or more embodiments, the particle size distribution of the support material is from 500 nm to 50 μm. The BET surface area of the support material in the fresh state is from 30 to 200 m 2 / g and 15-150m after aging at 1000℃ for 4 hours 2 / g, characterized by nitrogen adsorption at 77K.
[0039] "BET surface area" has its general meaning referring to the Brunauer-Emmett-Teller method of determining surface area by N2 adsorption.
[0040] One or more embodiments include a high surface area refractory metal oxide support comprising an active compound selected from the group consisting of: alumina, alumina-zirconia, alumina-ceria-zirconia, lanthanum oxide-alumina, lanthanum oxide-zirconia-alumina, barium oxide-alumina, barium oxide lanthanum oxide-alumina, barium oxide lanthanum oxide-neodymia oxide alumina, and alumina-ceria. Examples of composites containing oxygen storage components include, but are not limited to, ceria-zirconia, ceria-zirconia-lanthanum oxide. Reference to "ceria-zirconia composite" refers to a composite comprising ceria and zirconia without specifying the amounts of each component. Suitable ceria-zirconia composites include, but are not limited to, composites having, for example, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90% or even 95% ceria content. Some embodiments provide that the support comprises bulk ceria having a nominal ceria content of 100% (ie, >99% pure).
[0041] Reference to an oxygen storage component (OSC) refers to an entity that has multiple valence states and can actively react with an oxidant such as oxygen or nitrogen oxides under oxidizing conditions; or react with a reducing agent such as carbon monoxide (CO) or hydrogen under reducing conditions. Examples of suitable oxygen storage components include cerium oxide. Praseodymium oxide can also be included as an OSC. Delivery of the OSC to the carrier coating layer can be achieved by using, for example, mixed oxides. For example, cerium oxide can be delivered via a mixed oxide of cerium and zirconium and / or a mixed oxide of cerium, zirconium and neodymium. For example, praseodymium can be delivered via a mixed oxide of praseodymium and zirconium and / or a mixed oxide of praseodymium, cerium, lanthanum, yttrium, zirconium and neodymium.
[0042] Reference to "PGM" refers to platinum group metals, while "Pt" refers to platinum, "Pd" refers to palladium, and "Rh" refers to rhodium. It should be understood that these terms include not only the metallic forms of these PGMs, but also any metal oxide forms that are catalytically active for emissions reduction. The present invention also contemplates combinations of metals and catalytically active metal oxide forms.
[0043] Reference to a "gasoline particulate filter" refers to a filter that is sized and configured to capture particulates generated by the combustion reaction in a direct injection gasoline engine. For example, particulates may be captured by using a particulate (or soot) filter, by using a flow-through substrate having an internal tortuous path so that changes in the direction of particulate flow cause them to be dislodged from the exhaust stream, by using a metal substrate such as a corrugated metal support, or by other methods known to those skilled in the art. Other filtering devices may be suitable, such as pipes with rough surfaces that can knock particles out of the exhaust stream. Pipes with elbows may also be suitable.
[0044] An exemplary particulate filter is a wall-flow filter substrate. A wall-flow substrate that can be used to support a catalyst composition has a plurality of fine, substantially parallel gas flow channels extending along the longitudinal axis of the substrate. Typically, each channel is blocked at one end of the substrate body, with alternating channels blocked at the opposite end face. Such monolithic carriers may contain up to about 300 flow channels (or "cells") per square inch of cross-section, although the amount used may be much less. For example, the carrier may have about 7 to 300, more typically about 200 to 300, pores per square inch ("cpsi"). The pores may have a cross-section of a rectangular, square, circular, elliptical, triangular, hexagonal, or other polygonal shape. Wall-flow substrates typically have a wall thickness of 0.008-0.016 inches. Specific wall-flow substrates have a wall thickness of 0.010-0.012 inches.
[0045] Typical wall flow filters in commercial use are generally formed with lower wall porosity than the wall flow filters utilized in the present invention, for example about 42% to 65%. The pore size distribution of typical commercial wall flow filters is generally very broad, with the average pore size being less than 25 microns.
[0046] The porous wall flow filters used in the present invention are catalyzed in that the walls of the element have thereon or contain therein one or more catalytic materials. The catalytic material may be present solely on the inlet side of the element wall, solely on the outlet side, on both the inlet and outlet sides, or the wall itself may consist entirely or in part of the catalytic material. The present invention includes the use of washcoats of one or more catalytic materials and combinations of washcoats of one or more catalytic materials on the inlet and / or outlet walls of the element.
[0047] With regard to metal substrates, useful substrates may comprise one or more metals or metal alloys. The metal carrier may be in various shapes such as corrugated sheet or monolithic form. Specific metal carriers include heat-resistant metals and metal alloys such as titanium and stainless steel, as well as other alloys in which iron is a significant or major component. Such alloys may contain one or more of nickel, chromium and / or aluminum, and the total amount of these metals may advantageously account for at least 15wt% of the alloy, such as 10-25wt% of chromium, 3-8wt% of aluminum and up to 20wt% of nickel. These alloys may also contain a small or trace amount of one or more other metals such as manganese, copper, vanadium, titanium, etc. The surface of the metal carrier may be oxidized at high temperatures, such as 1000 degrees Celsius and higher, to improve the corrosion resistance of the alloy by forming an oxide layer on the surface of the carrier. Such high temperature induced oxidation may enhance the adhesion of the catalytic material to the carrier.
[0048] In one or more embodiments, the second composition comprises a second support material; and a second platinum group metal. In specific embodiments, the first and second support materials are independently selected from the group consisting of alumina, zirconia, ceria, silica, titania, rare earth metal oxides other than ceria, and mixtures thereof. In specific embodiments, the first and second PGMs are independently selected from the group consisting of platinum (Pt), palladium (Pd), rhodium (Rh), and mixtures thereof.
[0049] As used herein, the term "mixture" or "combination" refers to, but is not limited to, a combination in any physical or chemical form, such as a blend, solution, suspension, alloy, or composite.
[0050] In more specific embodiments, the second composition is the same as the first composition. In other more specific embodiments, the second composition is different from the first composition.
[0051] In one or more embodiments, the second PGM is Pt, or Pt and Pd, and the second PGM is used to convert NO in the exhaust gas intox , CO and hydrocarbons into N2, CO2 and H2O and oxidize particulate matter trapped on a gasoline particulate filter. In a specific embodiment, the particle size of Pt in the second composition is 2-20 nm, preferably 2-10 nm, more preferably 5-7 nm. In a specific embodiment, the second composition may contain about 50 wt% to about 99.9 wt% (including about 60 wt% to about 99.8 wt%, including about 70 wt% to about 99.6 wt%) of the support material based on the calcined weight of the second composition.
[0052] In one or more embodiments, the first PGM is Rh, or Rh and Pd, and the first PGM is used to convert NO in the exhaust gas into x , CO and hydrocarbons to N , CO , and H 2 O. In specific embodiments, the first composition may comprise from about 50 wt % to about 99.9 wt % (including from about 60 wt % to about 99.8 wt %, including from about 70 wt % to about 99.6 wt %) of the support material based on the calcined weight of the first composition.
[0053] In one or more embodiments, the second composition comprises at least one of cerium oxide, zirconium oxide, strontium oxide, strontium carbonate, strontium sulfate, barium oxide, barium carbonate, barium sulfate, and manganese oxide. In a specific embodiment, the second composition has a carbon content of 5-200 m / s as characterized by nitrogen adsorption at 77K after calcination at 1000°C in air for 4 hours. 2 ·g -1 , preferably 7-100m 2 ·g -1 , more preferably 10-70m 2 ·g -1 In a specific embodiment, the second composition further comprises alumina, hydrated alumina or doped alumina, wherein the dopant is at least one of cerium oxide, zirconium oxide, strontium oxide, strontium carbonate, strontium sulfate, barium oxide, barium carbonate, barium sulfate and manganese oxide.
[0054] In one or more embodiments, the second composition comprises at least one organic material such as acetic acid, oxalic acid, citric acid, tartaric acid, fumaric acid, lactic acid, malic acid, maleic acid, hexanol, octanol, decanol, cellulose, hydroxyethyl cellulose, methyl hydroxyethyl cellulose, starch, polyethylene, polypropylene, polystyrene, polyethylene oxide, polyethylene terephthalate, polybutylene terephthalate, polyvinyl chloride, polyvinyl alcohol, polyvinyl pyrrolidone, polymethyl methacrylate, polyamide, polycarbonate, or polyurethane.
[0055] The main catalytic layer can be formed in a single layer or multiple layers. In some cases, it may be appropriate to prepare a slurry of a catalytic material and use the slurry to form multiple layers on a carrier. The catalytic layer can be easily prepared by methods well known in the prior art. A representative method is listed below. The term "carrier coating" as used herein has the usual meaning in the art, i.e., a thin and adherent coating of a catalytic material or other material applied to a substrate carrier material (such as a honeycomb carrier component), the coating having sufficient pores to allow the treated gas flow to pass therethrough. Therefore, a "carrier coating layer" is defined as a coating comprising carrier particles. A "catalytic carrier coating layer" is a coating comprising carrier particles impregnated with a catalytic composition.
[0056] The primary catalytic layer can be readily prepared in the form of a layer on a support. For the first layer of a specific carrier coating, finely divided particles of a high surface area refractory metal oxide such as γ-alumina are dispersed in a suitable medium such as water to form a slurry. In order to add components such as precious metals (e.g., palladium, rhodium, platinum and / or combinations thereof), stabilizers and / or promoters, such components can be added to the slurry as a mixture of water-soluble or water-dispersible compounds or complexes. Usually when palladium is required, the palladium component is utilized in the form of a compound or complex to achieve dispersion of the component on the refractory metal oxide support. The term "palladium component" refers to any compound or complex, etc., which, when calcined or used, decomposes or otherwise converts to a catalytically active form, usually a metal or metal oxide. As long as the liquid medium used to impregnate or deposit the metal component on the refractory metal oxide support particles does not react adversely with the metal or its compound or complex or other components that may be present in the catalyst composition, and can be removed by the metal component by volatilization or decomposition when heated and / or vacuum is applied, a water-soluble compound or water-dispersible compound or complex of the metal component can be used. In some cases, the removal of the liquid is not completed until the catalyst is put into use and subjected to high temperatures during operation. It is usually economical and environmentally friendly to use aqueous solutions of soluble compounds or complexes of the noble metals. For example, suitable compounds are palladium nitrate or rhodium nitrate.
[0057] A suitable method for preparing any layer of the layered primary catalytic layer of the present invention is to prepare a mixture of a solution of the desired precious metal compound (e.g., a palladium compound) and at least one support such as a finely divided high surface area refractory metal oxide support (the support is dry enough to absorb substantially all of the solution to form a wet solid, which is then combined with water to form a coatable slurry). In one or more embodiments, the slurry is acidic, for example having a pH of about 2 to less than about 7. The pH of the slurry can be reduced by adding an appropriate amount of an inorganic or organic acid to the slurry. When the compatibility of the acid and the raw material is taken into account, a combination of the two can be used. Inorganic acids include, but are not limited to, nitric acid. Organic acids include, but are not limited to, acetic acid, propionic acid, oxalic acid, malonic acid, succinic acid, glutamic acid, adipic acid, maleic acid, fumaric acid, phthalic acid, tartaric acid, and citric acid, etc. Thereafter, if desired, a water-soluble or water-dispersible compound of an oxygen storage component such as a cerium-zirconium complex, a stabilizer such as barium acetate, and a promoter such as lanthanum nitrate can be added to the slurry.
[0058] In one or more embodiments, the primary catalytic layer has a washcoat loading of 10-170 g / L, preferably 25-150 g / L, more preferably 45-120 g / L.
[0059] In one or more embodiments, the secondary functional material layer has a loading of 1-15 g / L, preferably 1.5-12 g / L, more preferably 2-10 g / L.
[0060] In one or more embodiments, the secondary functional material can be supported in the form of particles. In other embodiments, the secondary functional material can be supported in the form of a liquid suspension.
[0061] In a preferred embodiment, the secondary functional material is loaded in particulate form via a gas phase carrier, i.e., "dry loaded," without the use of any liquid carrier. This dry loading can result in a distribution of the secondary functional material within the filter that more closely mimics the distribution of non-secondary functional materials that become loaded on the particulate filter during use. Catalyzed gasoline particulate filters applied using a "dry loaded" secondary functional material layer show significant improvements in the conversion of all three types of pollutants, particularly HC and CO. Surprisingly, it has been found that improvements in soot combustion are achieved in catalyzed gasoline particulate filters applied using a "dry loaded" secondary functional material layer.
[0062] After loading, the secondary functional material can take the form of a packed bed. For example, when the particulate filter is a wall-flow filter, the secondary functional material can form a packed bed relative to the wall of multiple channels opened at the inlet side. The packed bed can be formed in the channel opened at the inlet side and relative to the sealing material of the closed channel, i.e., toward the outlet end of the inlet channel. The packed bed is usually porous and usually gas permeable, and the size of the hole is to capture particulate matter such as soot in gasoline exhaust. The pores of the packed bed are usually smaller than the pores of the porous substrate of the particulate filter. As an alternative, or in addition, the packed bed may have more pores than the wall of the porous substrate (i.e., it can provide a high level of filtration by providing a long path length). The packed bed can extend along the wall of multiple channels opened at the inlet side. The packed bed can take the form of a layer or a membrane, such as a continuous layer or a membrane. The packed bed can extend along the entire length of multiple channel walls, or only along a portion of the length of the wall. The secondary functional material can be in the form of a porous coating rather than a packed bed, such as a coating applied as (i.e., derived from) a carrier coating slurry. The porous coating may be disposed in a wall flow filter in a manner similar to the packed bed discussed above.
[0063] According to one or more embodiments, another significant advantage is that by reducing D 90 A higher fresh filtration efficiency (FFE) can be achieved. In some embodiments, the second functional material composition particles have a D of 1-50 μm, preferably 2-25 μm, and more preferably 3-20 μm. 90 .
[0064] “D 90 " has its usual meaning as referring to the point in the cumulative particle size distribution at which the cumulative weight from small particle diameters reaches 90%. 90 The particle size distribution is measured by using a laser diffraction particle size distribution analyzer.
[0065] Other aspects include a method for treating exhaust gas from a gasoline engine, comprising providing a particulate filter according to the foregoing embodiments; and directing exhaust gas from the engine through the particulate filter. The exhaust gas contains unburned hydrocarbons, carbon monoxide, nitrogen oxides, and particulate matter. Example
[0066] The present invention is more fully illustrated by the following examples, which are set forth for the purpose of illustrating the present invention and should not be construed as limiting it. Unless otherwise indicated, all parts and percentages are by weight, and all weight percentages are expressed on a dry basis, which means that water content is not included, unless otherwise indicated. In each example, the support is cordierite.
[0067] Example 1 - Comparison
[0068] A gasoline particulate filter with catalytic material is prepared in two coatings: a coating starting at the inlet side and a coating starting at the outlet side. Prior art catalyst composites for coating gasoline particulate filters to oxidize particulate matter trapped in the filter at low temperatures and reduce nitrogen oxides, carbon monoxide and hydrocarbons contain platinum, palladium and rhodium with a total precious metal loading of 16.5 g / ft 3 The ratio of Pt / Pd / Rh is 5 / 6.5 / 5. 3 ), a micropore density of 300 micropores per square inch, a wall thickness of about 200 μm and a porosity of 63% and an average pore size of 19 μm as measured by mercury intrusion. The coating was prepared as follows:
[0069] The components applied from the outlet side were high surface area gamma-alumina, a ceria-zirconia composite with 40 wt% ceria as an oxygen storage component, palladium, rhodium, barium oxide, and zirconium oxide in concentrations of about 24.3%, 69.2%, 0.3%, 0.3%, 4.5%, and 1.4%, respectively, based on the calcined weight of the catalyst. The barium oxide was introduced as a hydroxide solution. The zirconium oxide was introduced as a nitrate solution. The total loading of the coating was 1.01 g / in 3 .
[0070] Rhodium in the form of a rhodium nitrate solution is impregnated onto a high surface area gamma-alumina and a ceria-zirconia composite by a planetary mixer (P-mixer) to form a wet powder while achieving incipient wetness. Palladium in the form of a palladium nitrate solution is impregnated onto a high surface area gamma-alumina and a ceria-zirconia composite by a planetary mixer (P-mixer) to form a wet powder while achieving incipient wetness. An aqueous slurry is formed. Barium solution and zirconium solution are added. The slurry is ground to a particle size of 90% of 5 microns. The slurry is then coated on the outlet side of a wall-flow cordierite filter using a deposition method known in the art. After coating, the filter and outlet coating are dried and then calcined at a temperature of 550° C. for about 1 hour to obtain a half-way coated catalytic filter.
[0071] The components applied from the inlet side are 50 wt% cerium dioxide, platinum, palladium, highly dispersed pseudo-boehmite A high surface area ceria-alumina composite of alumina hydrate and zirconium oxide (concentrations based on the calcined weight of the catalyst are 94.7%, 1.1%, 0.3%, 2.0% and 2.0%, respectively). Highly dispersible pseudo-boehmite Alumina hydrate was introduced as an aqueous dispersion. Zirconium oxide was introduced as an acetate solution. The total loading of the coating was 0.26 g / in 3 .
[0072] Platinum in the form of an amine complex solution is impregnated onto a high surface area cerium oxide-alumina composite by a planetary mixer (P-mixer) to form a wet powder while achieving incipient wetness. Palladium in the form of a palladium nitrate solution is impregnated onto a high surface area cerium oxide-alumina composite by a planetary mixer (P-mixer) to form a wet powder while achieving incipient wetness. An aqueous slurry is formed. Add The slurry was ground to a particle size of 90% 12 microns. The slurry was then applied to the inlet side of the intermediate coated catalytic filter using a deposition method known in the art. After coating, the filter and the outlet and inlet coatings were dried and then calcined at a temperature of 550°C for about 1 hour.
[0073] Example 2
[0074] The gasoline particulate filter with catalytic material is prepared in a double coating: a primary catalytic layer applied from the outlet side and a secondary functional material layer applied from the inlet side. The catalyst composite contains platinum, palladium and rhodium, with a total precious metal loading of 16.5 g / ft 3 The ratio of Pt / Pd / Rh is 5 / 6.5 / 5. 3 ), a micropore density of 300 micropores per square inch, a wall thickness of about 200 μm and a porosity of 63% and an average pore size of 19 μm as measured by mercury intrusion. The coating was prepared as follows:
[0075] The main catalytic layer applied from the outlet side is a high surface area gamma-alumina, ceria-zirconia composite with ceria as 40 wt% as oxygen storage component, palladium, rhodium, barium oxide and zirconium oxide in concentrations of about 24.3%, 69.2%, 0.3%, 0.3%, 4.5% and 1.4%, respectively, based on the calcined weight of the catalyst. The barium oxide is introduced as a hydroxide solution. The zirconium oxide is introduced as a nitrate solution. The total loading of the coating is 1.01 g / in 3 .
[0076] Rhodium in the form of a rhodium nitrate solution is impregnated onto a high surface area gamma-alumina and a ceria-zirconia composite by a planetary mixer (P-mixer) to form a wet powder while achieving incipient wetness. Palladium in the form of a palladium nitrate solution is impregnated onto a high surface area gamma-alumina and a ceria-zirconia composite by a planetary mixer (P-mixer) to form a wet powder while achieving incipient wetness. An aqueous slurry is formed. Barium solution and zirconium solution are added. The slurry is ground to a particle size of 90% of 5 microns. The slurry is then coated on the outlet side of a wall-flow cordierite filter using a deposition method known in the art. After coating, the filter and outlet coating are dried and then calcined at a temperature of 550° C. for about 1 hour to obtain an intermediate coated catalytic filter.
[0077] The secondary functional material layer applied from the inlet side is a high surface area cerium oxide-aluminum oxide composite with 50 wt.% cerium dioxide, platinum and palladium (concentrations are about 98.6%, 1.1% and 0.3% based on the calcined weight of the catalyst, respectively). Platinum in the form of an amine complex solution is impregnated onto the high surface area cerium oxide-aluminum oxide composite by a planetary mixer (P-mixer), followed by palladium in the form of a palladium nitrate solution to form a wet powder while achieving incipient wetness. The powder is then calcined at a temperature of 550°C for about 2 hours and dry ground to a particle size of 90% 5.1 microns, 50% 2.1 microns and 10% 0.8 microns, with a specific surface area (BET model, 77K nitrogen adsorption measurement) of 66 m after calcination in air at 1000°C for 4 hours. 2 ·g -1 The high surface area ceria-alumina composite containing PGM in powder form was mixed with a carrier gas and blown into the component from the inlet side at room temperature. The flow rate of the carrier gas was 575 kg / h. The loading of the secondary functional material layer was 0.26 g / in 3 .
[0078] Example 3
[0079] A catalytic gasoline particulate filter according to Example 2, wherein the secondary functional material layer applied from the inlet side is dry ground to a particle size of 90% 11.7 microns, 50% 4.2 microns and 10% 1.4 microns. The loading of the secondary functional material layer is 0.26 g / in 3 .
[0080] Example 4
[0081] The catalyzed gasoline particulate filter according to Example 1 was used as the middle-coated catalyzed filter.
[0082] The secondary functional material layer applied from the inlet side is barium sulfate. The barium sulfate powder has a particle size of 90% 4.8 μm, 50% 2.3 μm and 10% 0.9 μm, wherein the specific surface area (BET model, 77K nitrogen adsorption measurement) after calcination at 1000°C in air for 4 hours is 3 m 2 ·g -1 The loading of the secondary functional material layer is 0.26 g / in 3 .
[0083] Example 5 - Testing
[0084] The ability of the gasoline particulate filters according to Examples 1-4 to convert gaseous pollutants (unburned HC, CO and NOx) was evaluated by placing these catalytic filters in the first position behind a SGE 1.5L turbocharged gasoline direct injection engine (WLTC test) and the results are shown in Figure 1 The catalyzed gasoline particulate filter with the secondary functional material layer applied showed significant improvements in the conversion of all three types of pollutants, especially HC and CO.
[0085] In the SGE 1.5L turbocharged gasoline direct injection engine (WLTC test; PN engine output = 3.5 × 10 12 The filtration efficiency of Examples 1-4 in a fresh state (0 km, or out-of-box state) was measured at the first location after filtration of 0.26 g / in 2 and the results are shown in Figure 2. The filtration efficiency of the catalytic gasoline particulate filter with the secondary functional material layer applied thereto was shown to be improved by 20% compared to the prior art filter without the secondary functional material layer applied thereto. It is also noteworthy that at this relatively high washcoat loading (0.26 g / in 3 or 15 g / L), the difference in fresh filtration efficiency caused by the properties or particle size distribution of the secondary functional layer was mitigated, as Examples 14, 15 and 16 all showed comparable fresh filtration efficiencies.
[0086] Example 6
[0087] The gasoline particulate filter with catalytic material is prepared in a double coating: a primary catalytic layer applied from the outlet side and a secondary functional material layer applied from the inlet side. The catalyst composite contains platinum and palladium, with a total precious metal loading of 6.25 g / ft 3 The ratio of Pt / Pd / Rh is 4 / 1 / 0. 3 ), a micropore density of 200 micropores per square inch, a wall thickness of about 200 μm and a porosity of 55% and an average pore size of 19 μm as measured by mercury intrusion. The coating was prepared as follows:
[0088] The main catalytic layer applied from the outlet side is a high surface area 50 wt% ceria, platinum, palladium, highly dispersed pseudoboehmite A high surface area ceria-alumina composite of alumina hydrate and zirconium oxide (concentrations are about 94.7%, 1.1%, 0.3%, 1.9% and 1.9%, respectively, based on the calcined weight of the catalyst. Highly dispersible pseudo-boehmite Alumina hydrate was introduced as an aqueous dispersion. Zirconium oxide was introduced as an acetate solution. The total coating loading was 0.20 g / in 3 .
[0089] Platinum in the form of an amine complex solution is impregnated onto a high surface area cerium oxide-alumina composite by a planetary mixer (P-mixer) to form a wet powder while achieving incipient wetness. Palladium in the form of a palladium nitrate solution is impregnated onto a high surface area cerium oxide-alumina composite by a planetary mixer (P-mixer) to form a wet powder while achieving incipient wetness. An aqueous slurry is formed. Add The slurry was ground to a particle size of 90% 12 microns. The slurry was then applied to the outlet side of a wall-flow cordierite filter using a deposition method known in the art. After coating, the filter and outlet coating were dried and then calcined at a temperature of 550°C for about 1 hour.
[0090] The secondary functional material layer applied from the inlet side is a high surface area cerium oxide-aluminum oxide composite with 50 wt.% cerium dioxide, platinum and palladium (concentrations are 98.6%, 1.1% and 0.3% based on the calcined weight of the catalyst, respectively). Platinum in the form of an amine complex solution is impregnated onto the high surface area cerium oxide-aluminum oxide composite by a planetary mixer (P-mixer), followed by palladium in the form of a palladium nitrate solution to form a wet powder while achieving incipient wetness. The powder is then calcined at a temperature of 550°C for about 2 hours and dry ground to a particle size of 90% 5.1 microns, 50% 2.1 microns and 10% 0.8 microns, with a specific surface area (BET model, 77K nitrogen adsorption measurement) of 66 m after calcination in air at 1000°C for 4 hours. 2 ·g -1 The high surface area cerium oxide-aluminum oxide composite containing PGM in powder form was mixed with a carrier gas and blown into the component from the inlet side at room temperature. The flow rate of the carrier gas was 575 kg / h. The loading of the secondary functional material layer was 0.06 g / in 3 .
[0091] Example 7
[0092] A catalyzed gasoline particulate filter according to Example 6, wherein the slurry of the primary catalytic layer is ground to a particle size of 90% of 5 microns.
[0093] Example 8
[0094] A gasoline particulate filter with catalytic material was prepared using a single coating method from the inlet side. The catalyst composite contained platinum and palladium with a total precious metal loading of 6.25 g / ft 3 The ratio of Pt / Pd / Rh is 4 / 1 / 0. 3 ), a micropore density of 200 micropores per square inch, a wall thickness of about 200 μm and a porosity of 55% and an average pore size of 19 μm as measured by mercury intrusion. The coating was prepared as follows:
[0095] The catalytic material applied from the inlet side is a high surface area cerium oxide-alumina composite with 50 wt.% cerium oxide, platinum and palladium (concentrations are 98.6%, 1.1% and 0.3% respectively based on the calcined weight of the catalyst). Platinum in the form of an amine complex solution is impregnated onto the high surface area cerium oxide-alumina composite by a planetary mixer (P-mixer), followed by palladium in the form of a palladium nitrate solution to form a wet powder while achieving incipient wetness. The powder is then calcined at a temperature of 550°C for about 2 hours and dry ground to a particle size of 90% of 5.1 microns, 50% of 2.1 microns and 10% of 0.8 microns, with a specific surface area (BET model, 77K nitrogen adsorption measurement) of 66 m after calcination in air at 1000°C for 4 hours. 2 ·g -1 The high surface area cerium oxide-aluminum oxide composite containing PGM in powder form was mixed with a carrier gas and blown into the component from the inlet side at room temperature. The flow rate of the carrier gas was 575 kg / h. The loading of the secondary functional material layer was 0.26 g / in 3 .
[0096] Example 9 - Testing
[0097] In the SGE 1.5L turbocharged gasoline direct injection engine (WLTC test; PN engine output = 3.5 × 10 12 The gas phase pollutant conversion capacity and filtration efficiency of Examples 6-8 in a fresh state (0 km, or out-of-box state) were measured in the first position after # / km) and the results are shown in Figure 3 and Figure 4 Similar fresh filtration efficiencies were observed in these examples and the catalytic filters having both a primary catalytic layer and a secondary functional material layer (Examples 6 and 7) showed significantly better TWC activity than the sample loaded with powder only (Example 8).
[0098] Example 10 - Comparison
[0099] A gasoline particulate filter with catalytic material was prepared by single coating from the inlet side. The prior art three-way conversion (TWC) catalyst composite contains palladium and rhodium, with a total noble metal loading of 7 g / ft 3 The ratio of Pt / Pd / Rh is 0 / 2 / 5. 3 ), a micropore density of 300 micropores per square inch, a wall thickness of about 200 μm and a porosity of 63% and an average pore size of 19 μm as measured by mercury intrusion. The coating was prepared as follows:
[0100] The components applied from the inlet side were a high surface area gamma-alumina, a ceria-zirconia composite with 40 wt% ceria as an oxygen storage component, palladium, rhodium, barium oxide, and zirconium oxide in concentrations of about 24.8%, 68.7%, 0.1%, 0.2%, 5.0%, and 1.3%, respectively, based on the calcined weight of the catalyst. The barium oxide was introduced as a hydroxide solution. The zirconium oxide was introduced as a nitrate solution. The total loading of the coating was 1.23 g / in 3 .
[0101] Rhodium in the form of a rhodium nitrate solution is impregnated onto a high surface area gamma-alumina and a ceria-zirconia composite by a planetary mixer (P-mixer) to form a wet powder while achieving incipient wetness. Palladium in the form of a palladium nitrate solution is impregnated onto a high surface area gamma-alumina and a ceria-zirconia composite by a planetary mixer (P-mixer) to form a wet powder while achieving incipient wetness. An aqueous slurry is formed. Barium solution and zirconium solution are added. The slurry is ground to a particle size of 90% 5 microns. The slurry is then coated on the inlet side of a wall flow cordierite filter using a deposition method known in the art. After coating, the filter and inlet coating are dried and then calcined at a temperature of 550°C for about 1 hour.
[0102] Embodiment 11
[0103] A catalyzed gasoline particulate filter according to Example 10, wherein a prior art three-way conversion (TWC) catalyst composite is the primary catalytic layer and an additional secondary functional material layer is supported on the inlet side of the filter.
[0104] The secondary functional material layer applied from the inlet side is high surface area gamma-alumina. The alumina is dry ground to a particle size of 90% 5 μm, 50% 2.5 μm and 10% 1 μm, with a specific surface area (BET model, 77K nitrogen adsorption measurement) of 70 m after calcination at 1000°C in air for 4 hours. 2 ·g -1The high surface area gamma-alumina composite in powder form was mixed with a carrier gas and blown into the component at room temperature. The flow rate of the carrier gas was 575 kg / h. The loading of the secondary functional material layer was 0.066 g / in 3 .
[0105] Example 12
[0106] The catalytic gasoline particulate filter according to Example 11, wherein the loading amount of the secondary functional material layer is 0.041 g / in 3 .
[0107] Embodiment 13
[0108] The catalytic gasoline particulate filter according to Example 11, wherein the loading amount of the secondary functional material layer is 0.024 g / in 3 .
[0109] Embodiment 14
[0110] A catalytic gasoline particulate filter was prepared in the same manner as in Example 11, wherein the applied secondary functional layer was a high surface area gamma-alumina. The alumina was dry ground to a particle size of 90% 16 microns, 50% 6.9 microns and 10% 2.0 microns, wherein the specific surface area (BET model, 77K nitrogen adsorption measurement) after calcination at 1000°C in air for 4 hours was 76 m 2 ·g -1 The loading amount of the secondary functional material layer is 0.066g / in 3 .
[0111] Embodiment 15
[0112] A catalytic gasoline particulate filter was prepared in the same manner as in Example 11, wherein the applied secondary functional layer was a high surface area gamma-alumina. The alumina was dry ground to a particle size of 90% 25.4 μm, 50% 10.9 μm and 10% 2.4 μm, wherein the specific surface area (BET model, 77K nitrogen adsorption measurement) after calcination at 1000°C in air for 4 hours was 75 m 2 ·g -1 The loading amount of the secondary functional material layer is 0.066g / in 3 .
[0113] Example 16
[0114] A catalytic gasoline particulate filter was prepared in the same manner as in Example 11, wherein the applied secondary functional layer further comprised polyvinyl alcohol powder. Polyvinyl alcohol PVA-1788 was obtained in the form of a fine powder having a particle size of 230 mesh. The PVA powder was premixed with dry-ground high surface area gamma-alumina at a weight ratio of 1:5. The mixed powder was further mixed with a carrier gas and blown into the component at room temperature. The flow rate of the carrier gas was 575 kg / h. The total loading of the secondary functional material layer was 0.079 g / in 3 .
[0115] Example 17 - Testing
[0116] In the first position (SGE 1.5L turbocharged gasoline direct injection engine; WLTC test; PN engine output = 3.5 × 10 12 The filtration efficiency of Examples 10-16 in a fresh state (0 km, or out-of-box state) was measured and the results are shown in Figure 5 The catalyzed gasoline particulate filter with the secondary functional material layer applied thereto exhibits a significant increase in filtration efficiency compared to prior art filters without the secondary functional material layer applied thereto. Notably, at temperatures as low as 0.024 g / in 3 At a functional layer loading of 100%, the filtration efficiency increase is already very significant (+24%, Example 10 vs. 13). In addition, as shown in Examples 11 and 12, the filtration efficiency of the examples according to the embodiments of the present invention is further improved by applying a higher loading of the secondary functional material layer. Examples 11, 14 and 15 demonstrate the optimized particle size distribution of the functional layer, where the higher filtration efficiency (FFE) is achieved by increasing the particle size D 90 This was achieved by reducing the particle size from 25 μm to 16 μm and further to 5 μm. With the addition of organic material (in Example 16), the catalyzed gasoline particulate filter prepared according to this example maintained its high filtration efficiency.
Claims
1. A catalytic particulate filter for gasoline engine exhaust, comprising: (1) Gasoline particulate filter (GPF); (2) a primary catalytic layer coated on or within the inlet side, outlet side, or both sides of the GPF surface, the primary catalytic layer comprising a first composition, wherein the first composition comprises a first support material and a first platinum group metal (PGM); and (3) A secondary catalytic layer disposed on or within the inlet side, outlet side, or both sides of the GPF surface; the secondary catalytic layer comprises a second composition, wherein the secondary catalytic layer is supported in the form of particles via a gas phase carrier, and wherein the particles of the second composition have a D of 2-25 μm. 90 ; where "D 90 ” refers to the point in the cumulative particle size distribution where the cumulative weight from small particle diameters reaches 90%; (4) wherein the primary catalytic layer has a higher loading than the secondary catalytic layer; (5) The secondary catalytic layer is placed on top of the primary catalytic layer, or the primary catalytic layer is placed on top of the secondary catalytic layer; wherein the second composition comprises a second support material and a second platinum group metal (PGM), wherein the first and second support materials are independently selected from the group consisting of alumina, zirconia, ceria, silica, titania, rare earth metal oxides other than ceria, and mixtures thereof, and wherein the first and second PGMs are independently selected from the group consisting of platinum (Pt), palladium (Pd), rhodium (Rh), and mixtures thereof; or wherein the second composition comprises at least one of cerium oxide, zirconium oxide, strontium oxide, strontium carbonate, strontium sulfate, barium oxide, barium carbonate, barium sulfate, manganese oxide, or aluminum oxide, wherein the first support material is independently selected from the group consisting of aluminum oxide, zirconium oxide, cerium oxide, silicon dioxide, titanium dioxide, rare earth metal oxides other than cerium oxide, and mixtures thereof, and the first PGM is independently selected from the group consisting of platinum (Pt), palladium (Pd), rhodium (Rh), and mixtures thereof; And wherein the platinum group metal includes any metal oxide form that is catalytically active for emissions reduction.
2. The catalytic particulate filter according to claim 1, wherein the second PGM is Pt, or a mixture of Pt and Pd, and the second PGM is used to convert NO in the exhaust gas into x A catalytically effective amount is present to convert N2, CO and hydrocarbons into N2, CO2 and H2O and to oxidize particulate matter trapped on a gasoline particulate filter.
3. The catalytic particulate filter according to claim 1, wherein the first PGM is Rh, or a mixture of Rh and Pd, and the first PGM is used to convert NO in the exhaust gas into x , CO and hydrocarbons are present in a catalytically effective amount for converting N2, CO2 and H2O.
4. The catalytic particulate filter according to claim 2, wherein the first PGM is Rh, or a mixture of Rh and Pd, and the first PGM is used to convert NO x , CO and hydrocarbons are present in a catalytically effective amount for converting N2, CO2 and H2O.
5. The catalyzed particulate filter of claim 1, wherein the second composition has a relative humidity of 5-200 m / s as characterized by 77K nitrogen adsorption after calcination at 1000°C in air for 4 hours. 2 ·g -1 BET specific surface area.
6. The catalyzed particulate filter of claim 1, wherein the second composition has a relative humidity of 7-100 m / s as characterized by 77K nitrogen adsorption after calcination in air at 1000°C for 4 hours. 2 ·g -1 BET specific surface area.
7. The catalyzed particulate filter of claim 1, wherein the second composition has a relative humidity of 10-70 m / s as characterized by 77K nitrogen adsorption after calcination at 1000°C in air for 4 hours. 2 ·g -1 BET specific surface area.
8. The catalyzed particulate filter of claim 5, wherein the second composition further comprises alumina, hydrated alumina, or doped alumina, wherein the dopant is at least one of cerium oxide, zirconium oxide, strontium oxide, strontium carbonate, strontium sulfate, barium oxide, barium carbonate, barium sulfate, and manganese oxide.
9. The catalyzed particulate filter of claim 6, wherein the second composition further comprises alumina, hydrated alumina, or doped alumina, wherein the dopant is at least one of cerium oxide, zirconium oxide, strontium oxide, strontium carbonate, strontium sulfate, barium oxide, barium carbonate, barium sulfate, and manganese oxide.
10. The catalyzed particulate filter of claim 7, wherein the second composition further comprises alumina, hydrated alumina, or doped alumina, wherein the dopant is at least one of cerium oxide, zirconium oxide, strontium oxide, strontium carbonate, strontium sulfate, barium oxide, barium carbonate, barium sulfate, and manganese oxide.
11. The catalyzed particulate filter according to any one of claims 1 to 10, wherein the second composition further comprises an organic material selected from one or more of the following groups: acetic acid, oxalic acid, citric acid, tartaric acid, fumaric acid, lactic acid, malic acid, maleic acid, hexanol, octanol, decanol, cellulose, hydroxyethyl cellulose, methyl hydroxyethyl cellulose, starch, polyethylene, polypropylene, polystyrene, polyethylene oxide, polyethylene terephthalate, polybutylene terephthalate, polyvinyl chloride, polyvinyl alcohol, polyvinyl pyrrolidone, polymethyl methacrylate, polyamide, polycarbonate or polyurethane.
12. The catalyzed particulate filter according to any one of claims 1 to 10, wherein the primary catalytic layer has a washcoat loading of 10 to 170 g / L.
13. The catalyzed particulate filter of claim 11, wherein the primary catalytic layer has a washcoat loading of 10-170 g / L.
14. The catalyzed particulate filter of claim 13, wherein the primary catalytic layer has a washcoat loading of 25-150 g / L.
15. The catalyzed particulate filter of claim 13, wherein the primary catalytic layer has a washcoat loading of 45-120 g / L.
16. The catalyzed particulate filter according to any one of claims 1 to 10, wherein the secondary catalytic layer has a loading of 1 to 15 g / L.
17. The catalyzed particulate filter according to any one of claims 13 to 15, wherein the secondary catalytic layer has a loading of 1 to 15 g / L.
18. The catalyzed particulate filter of claim 17, wherein the secondary catalytic layer has a loading of 1.5-12 g / L.
19. The catalyzed particulate filter of claim 17, wherein the secondary catalytic layer has a loading of 2-10 g / L.
20. The catalyzed particulate filter according to any one of claims 1 to 10, wherein the second composition particles have a D 90 .
21. The catalyzed particulate filter according to claim 18 or 19, wherein the second composition particles have a D 90 .
22. A method for treating exhaust gas from a gasoline engine, comprising: (1) providing a catalyzed particulate filter according to any one of claims 1 to 21, and (2) Directing engine exhaust through a particulate filter.
23. The method of claim 22, wherein the exhaust gas contains unburned hydrocarbons, carbon monoxide, nitrogen oxides and particulate matter.
Citation Information
Patent Citations
Removal of particulates from the exhaust gas of internal combustion engines operated with a predominantly stoichiometric air / fuel mixture
US8066963B2
Gasoline engine emissions treatment systems having particulate traps
US8173087B2
Gasoline engine emissions treatment systems having particulate filters
US8815189B2
Treatment system for gasoline engine exhaust gas
CN102574056A
Particle filter with a plurality of coatings
CN113366202A